Síntese in situ pelo método Pechini de compósitos magnetoelétricos SBN/NFO para o controle do crescimento anormal dos grãos da fase SBN - Muñoz Hoyos, José Rodrigo (2016)
A study was made of the synthesis and processing of magnetoelectric particulate composites of strontium barium niobate (SrxBa1-xNb2O6, or simply SBN) as a lead-free piezoelectric phase and nickel ferrite (NFO) as a magnetic phase. The specific objectives of this work were: (i) to obtain SBN (TBT) and NFO phases without impurities during the synthesis of the powders and the densification of the ceramic bodies; (ii) to produce SBN-NFO composites of 0–3 connectivity, i.e., with a highly homogeneous distribution of ferrite phase in the SBN matrix; and (iii) to ensure mechanical interphase coupling based on high densification, without the occurrence of anomalous SBN grain growth. The Sr0.61Ba0.39Nb206/NiFe2O4 biphasic system (SBN61/NFO) was prepared with molar ratios of 50/50, 70/30 and 80/20 by means of in situ chemical synthesis using the Pechini method. The objectives of this work included an analysis and proposal of phase formation during the in situ synthesis of SBN/NFO grain growth, with high chemical homogeneity, a low degree of NFO phase percolation, and 0–3 connectivity. composites. The synthesized powders were analyzed by Rietveld refinement of their X-ray diffraction patterns. This enabled the quantification of spurious phases and revealed the effect of reducing these phases and the abnormal grain growth resulting from the increased proportion of NFO phase. However, the secondary phases could only be determined based on the hypotheses put forward in the proposal of the phase formation model of the SBN/NFO system. This proposed phase formation model enabled us to understand why SBN and NFO phases can be formed simultaneously during in situ synthesis by the Pechini method, and also to conclude that the presence of precipitates during the formation of the polymeric resin may be the cause of spurious phases. This allowed us to propose changes in the synthesis step in order to eliminate possible precipitates, which actually resulted in the reduction of the secondary phases in the tests of the 70/30 system. After sintering, magnetoelectric composites were obtained with a relative density of ~96%, without abnormal grain growth, with high chemical homogeneity, a low degree of NFO phase percolation, and 0–3 connectivity.